2017
DOI: 10.2134/jeq2016.10.0411
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Road Salting on Water Quality in Fractured Crystalline Bedrock

Abstract: Many rural communities depend on bedrock wells as a primary water source, which raises the issue as to whether increasing amounts of salt application are affecting bedrock water quality and to what degree. Through wellbore profiling, this study investigated changes in specific conductance in two crystalline bedrock wells at the University of Connecticut in Storrs, CT, from 2003 to 2016, with particular emphasis on the impacts of increased salt application with a change in deicing practices at the university af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Underlying hydrogeology can influence the movement and residence of subsurface Clcontamination and transport of radionuclides. Chloride was highly persistent in fractured bedrock in Connecticut, USA and concentrations accumulated in groundwater over time due to road salts (Vitale et al 2017). In the Northeastern US, Na ?…”
Section: Identifying Risks Of Fss Based On Presence Of Radionuclides and Hydrogeologymentioning
confidence: 99%
“…Underlying hydrogeology can influence the movement and residence of subsurface Clcontamination and transport of radionuclides. Chloride was highly persistent in fractured bedrock in Connecticut, USA and concentrations accumulated in groundwater over time due to road salts (Vitale et al 2017). In the Northeastern US, Na ?…”
Section: Identifying Risks Of Fss Based On Presence Of Radionuclides and Hydrogeologymentioning
confidence: 99%
“…Recent research has also utilized analytic approaches to estimate chloride applications in recharge based on land use (Betts et al, 2015) and has identified seasonal variability in the data (Rotaru et al, 2014). Vitale et al (2017) identified inflections in chloride increases through time and posited that these inflections indicate major changes in application rates or pathways for chloride to enter the aquifer. However, we are unaware of any attempt to model the transient forces behind chloride accumulation and variability.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in salinity of water characterized by the increase in chloride ions concentrations signals changes in the quality of the biotope and the risks of biocenosis settling such reservoirs [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the periods of thaws, especially in early spring, when melting snow and ice cover of city streets flow into the tank substantial amounts of chloride ions. In this case the changes in chloride concentrations are seasonal [5][6][7][8][9][10][11][12][13][14][15]. Generally, in recent years we have seen an increase in the concentration of chloride ions in freshwater bodies of water around the world [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%